The Implementation of Folklore based Mind Mapping Technique in Teaching Students' Writing Skill - rasidin, gian amara (ELITE JOURNAL, 2024)
This research aimed to prove significantly effective or not to used mind mapping technique in teaching writing skill. This research used a pre-experimental design with one group pre- test and post-test. The population were all of the eighth grade students of SMP Negeri 8 Lubuklinggau with consist that 213 students. The sampling technique used cluster random sampling with method of lottery and the sample selected was VIII.F clas with consist 29 students. The data for this research was collected by used written test. Technique for collecting the data were the researcher classifying individual score students. Then, the researcher used the minimum mastery criteria to convert students’ score ability in writing. Next, the researcher used normality test to find out the data and finally the researcher used match t-test to find out the hypothesis. The researcher found that The Implementation of Folklore Based Mind Mapping Techniques in Teaching Students’ Writing Skill at SMP Negeri 8 Lubuklinggau was effective. It could be proved by the significant difference between the mean score in the pre-test and post-test. The mean score of the students in the pre-test was 43.00 and in the post test was 76.05. The t-obtained was 5.19, it was higher than 1.701 as the critical value in t-table. Therefore, it was clearly stated that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Keywords: Foklore, Mind Mapping Technique, Teaching Students’, Writing Skill, Narrative Text.